The Role of T Helper 17 Cells and Other IL-17-Producing Cells in Bone Resorption and Remodeling. (25th May 2015) - Liu, Wen-Xing; Li, Zhi-Jun; Niu, Xiu-Long; Yao, Zhi; Deng, Wei-Min
<x xml:space="preserve">Abstract</x> In recent decades, many studies have highlighted the role of IL-17-producing cells in bone resorption. However, the importance of many IL-17-producing cell types remains largely unknown in bone remodeling. In this review, we summarize the function of IL-17-producing cells, with a focus on T helper 17 (Th17) cells, in bone resorption and remodeling.